Studying electro-physical characteristics of detecting elements on the ohmic side of silicon microstrip detector - Maslov, N.I.; Potin, S.M.; Starodubtsev, A.F. (Вопросы атомной науки и техники, 2005)
The results of studying the ohmic side of the double-sided microstrip detectors (DSMD) possessing the diode separating p⁺ stop structure of different type and size are presented. The effect of the p⁺ stop structure on the DSMD interstrip resistance and interstrip capacitance is considered.